Synthesis and Coordination Behavior of 9,10-Diarsatriptycene - Inaba, Ryoto; Kikuchi, Takashi; Imoto, Hiroaki; Naka, Kensuke (Synlett, 2023)
Herein, 9,10-diheterotriptycenes (DHTs) containing heavy pnictogens (Pn, Pn = As, Sb, and Bi) are synthesized without using the dangerous chemicals used in conventional synthetic methods: tert-butyllithium, organomercury reagents, or trichloroarsine. In particular, 9,10-diarsatriptycene is obtained in relatively high yield and is stable under oxidation and coordination reactions. Additionally, the gold chloride complex 9,10-diarsatriptycene forms a one-dimensional supramolecular polymer constructed through coordination and aurophilic interactions.
Keywords: diheterotriptycene; pnictogen; practical synthesis; oxidation; coordination; supramolecular polymer